Myoepithelioma of the Soft Palate: A Case Report. (2nd October 2013) - Yadav, Ajay Kumar; Nadarajah, Jeyaseelan; Chandrashekhara, S. H.; Tambade, Vishal Dnyandeo; Acharya, Sudeep
Abstract : Myoepitheliomas are rare benign tumors of myoepithelial cell origin, most commonly seen in parotid gland. These tumors are also reported in oral cavity, soft palate being the most common site of involvement. Imaging findings are nonspecific, and histopathology is necessary to differentiate from other tumors. Our case showed mildly enhancing well-circumscribed mass in soft palate with histological findings consistent with myoepithelioma. The aim of this case report is to increase the awareness about this rare benign tumor regarding its morphological, histopathological, and radiological features along with its possible differential diagnosis.